A 3D spatial data model of the solar rights associated with individual residential properties. (March 2019) - Li, Lin; Lei, Yuan; Tang, Lei; Yan, Fen; Luo, Feng; Zhu, Haihong
Abstract: Increased residence in high-rise buildings has aroused demand for sunlight or sunlight duration because a lack of sunlight may lead to negative effects on the mental health of the residents of high-rise buildings. To address this issue, many countries have already enacted laws, regulations and standards that ensure solar rights for residents by guaranteeing a certain duration of sunlight. However, feasible methods that clearly describe the temporal-spatial properties of solar rights for residential buildings are presently lacking, especially for individual housing units distributed in high-rise buildings. Consequently, no relevant data model exists in any current cadastral database. This study presents a 3D data model that incorporates a range of data elements to represent the temporal-spatial extent of solar rights in the context of the current legal system of China. Using existing legal stipulations and spatial features, solar rights are classified into solar easements and neighbouring solar rights, which are separately described by geometric elements developed from the relevant legal stipulations. In addition, the geometric elements of the model are systematically integrated with existing property elements to enable the description of solar rights associated with individual residential properties. To enable the use of this model in a wide range of applications, the model is extended from the Land Administration Domain Model (LADM) and implemented using CityGML application domain extensions (ADEs). The experiments described in this study demonstrate the utility of the 3D data model for the spatial clarification of the solar rights associated with individual 3D properties. Highlights: A 3D spatial data model of solar rights associated with individual residential properties is proposed. Solar rights are divided into solar easements and neighbouring solar rights. The model is extended from the Land Administration Domain Model and implemented by CityGML. The proposed model can be integrated to current cadastral database.